2011
DOI: 10.1017/s0267190511000043
|View full text |Cite
|
Sign up to set email alerts
|

Research in Language-Literature Instruction: Meeting the Call for Change?

Abstract: The purpose of this review is to assess whether recent scholarship on language-literature instruction—the deliberate integration of language development and literary study at all levels of the foreign language curriculum—within the context of U.S. institutions of higher education reflects shifts in thinking regarding the role of literature in foreign language curricula. These shifts have come in response to the 2007 Report of the Modern Language Association Ad Hoc Committee on Foreign Languages, which recommen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 65 publications
0
29
0
Order By: Relevance
“…These studies in the Arabic context often identified a mixed attitude toward literature in Arabic-speaking communities. However, scholars outside the Arab world (Tehan, Yuksel, & Inan, 2015;Babaee & Yahya, 2014;Lakshmi & Jayachandran, 2012;Paesani, 2011;Fogal, 2010;Ghazali et al, 2009;Ögeyik, 2007) have recently and vehemently highlighted the role of literature in language learning and teaching. Literature occupies a central place in language learning.…”
Section: Related Studies In the Arab World And Beyondmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies in the Arabic context often identified a mixed attitude toward literature in Arabic-speaking communities. However, scholars outside the Arab world (Tehan, Yuksel, & Inan, 2015;Babaee & Yahya, 2014;Lakshmi & Jayachandran, 2012;Paesani, 2011;Fogal, 2010;Ghazali et al, 2009;Ögeyik, 2007) have recently and vehemently highlighted the role of literature in language learning and teaching. Literature occupies a central place in language learning.…”
Section: Related Studies In the Arab World And Beyondmentioning
confidence: 99%
“…The authors highlighted different techniques that can be of great help for teachers and learners alike. Paesani (2011) reviewed the research on different models that include literature as a necessary part of the curricula. Her review of scholarly studies in the field suggested that language in literature and literature in language courses can lead to a shift toward a multimodal language development.…”
Section: Related Studies In the Arab World And Beyondmentioning
confidence: 99%
“…Researchers have noted that literature courses such as those that make up the senior levels of foreign language programmes have little if any systematic focus on language development (Paesani, 2011), while lower-level courses typically focus on the development of oral communicative competence and grammar/vocabulary (form). Such a divide suggests that transition courses need to address tasks that not only are familiar to freshman and sophomores, but that also help socialise undergraduates into the types of tasks they will be required to undertake in more advanced content/literature classes.…”
Section: Resultsmentioning
confidence: 99%
“…The present study focuses on the third-year Spanish course. Scholars have argued that the language-content or languageliterature 'gap' that exists between courses in the basic-intermediate and upper-level course sequences often makes third-year language learning problematic (Brandes & Rettig, 1986;Brown, Bown, & Egget, 2009;Kraemer, 2008;Lord, 2014;Paesani, 2011). Students who are used to learning the grammatical and lexical patterns in beginning and intermediate courses need help learning to function in upper-level courses, which tend to focus primarily on content, typically literature (Zyzik & Polio, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation